2013
DOI: 10.1080/10941665.2013.838180
|View full text |Cite|
|
Sign up to set email alerts
|

Attitude Towards Green Hotel by Hoteliers and Travel Agency Managers in Taiwan

Abstract: Analysis is performed by green hotel features: energy conservation, water conservation, waste management, green purchasing, and corporate social responsibility. Questionnaires were distributed to managers of hotels and travel agencies via snowball-sampling. Findings show that hoteliers have higher green hotel attitudes than travel agency managers. By gender, female managers have higher green hotel attitudes. Managers with less work experience have higher green hotel attitudes. Managers who work for upscale hot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 26 publications
0
27
1
Order By: Relevance
“…This is simply because the installation of sensors does not require high costs and the installed system provides significant cost advantages for the hotel. Kung and Lee [86] evaluated the development of environmental measures by managers of international tourist hotels in Taiwan. The researchers revealed that environmental measures have primarily been limited to energy and water conservation in most of the major hotels in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…This is simply because the installation of sensors does not require high costs and the installed system provides significant cost advantages for the hotel. Kung and Lee [86] evaluated the development of environmental measures by managers of international tourist hotels in Taiwan. The researchers revealed that environmental measures have primarily been limited to energy and water conservation in most of the major hotels in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…In response to consumers' increasing awareness of environmental topics, incorporating environmentally-friendly ideas in restaurant management is progressing as a trend [64]. More education regarding environmentalism may need to be introduced to consumers by the government across different sectors, such as schools, enterprises and public organizations [76], with the intent to improve the awareness of environmentalism among the public so that consumers will be willing to pay for green products. Therefore, educators must be conscious that advocating sustainable service innovation notions to students will help take shape the base of future restaurant management.…”
Section: Discussionmentioning
confidence: 99%
“…Despite effects or pressures coming from inside or outside, in some cases hoteliers faced the problem of what to do? Citing, Zurburg, et al (1995) study, Tsai, et al (2014 survey results of hoteliers, found that most of the hoteliers in the sample were not sure how to proceed with the needed actions and precautions for environmental activities (Tsai, et al, 2014(Tsai, et al, : 1093. On the other hand, written literature on sustainability practices may show different examples including hotel personnel performing sustainability activities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Theoretically and practically there is a general belief that size or performance of companies will effect the content of environmental practices of tourist establishments. At this point in time, it is possible to find studies showing positive or negative relationships between size/ degree of environmental practices and performance (Tsai, et al, 2014(Tsai, et al, : 1093. Today, sustainability practices can be seen everywhere in business types from hotels to airlines to entire tourist destinations.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation